Facebook usage and functionality as the predictive factors in contributing towards employee engagement - Abd Latib, Latifah; Bolong, Jusang; Ahmad Ghazali, Akmar Hayati (Elsevier, 2014)
Although it is clear that Facebook is a very powerful tool of communication, many employers are unable to identify the Facebook usage and functionality in engaging their employees. Therefore, a quantitative survey involved 55 respondents using purposive sampling technique has been done to determine whether Facebook usage and functionality are the predictive factors in contributing towards employee engagement. Based on multiple regression analysis, it showed that groups, presence and reputations (functionality) and perceived ease-of-use (Usage) are the predictive factors in engaging the employees. As conclusion, by analyzing these predictive factors, organizations can understand how Facebook activities certainly benefit to them in engaging their employees.